Medical and Pharmacy Students’ Attitudes Towards Physician-Pharmacist Collaboration in Indonesia: A Case Study Approach - Nisa Febrinasari; Hudan Taufiq; Futikha Hudaningrum (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Learning process evaluation of Interprofessional Education (IPE) was crucial to determine the implementation process’s success. The evaluation can be done by researching student attitudes in IPE activities. Research on students' attitudes in medical education and pharmacy study programs is expected to be a guideline for the IPE curriculum drafting team at the Faculty of Medicine, Universitas Islam Sultan Agung, Semarang, to develop future IPE learning activities. The study design was observational analytic with a cross-sectional method involving all medical and pharmacy students of the Faculty of Medicine, Universitas Islam Sultan Agung who had participated in a Small Group Discussion with TB management and met the inclusion criteria. Data collection was carried out in August 2020 using an online google form questionnaire. Data obtained through the Scale of Attitudes Toward Psychic-Pharmacist Collaboration questionnaire contains 16 questions tested for validity and reliability. Questions were answered using a 4-point Likert Scale. The statistical test analysis results on the total score of the collaboration attitude scale using the Mann Whitney Test was a p-value of 0.000. The median total score of medical and pharmacy students was 47.00 and 56.00, respectively. The p-value indicates a significant difference between the total scores of medical and pharmacy students. Based on the analysis results, the study shows significant differences in collaboration attitudes. Medical education students fall into the